Strategi Peningkatan Literasi dan Minat Belajar Siswa: Studi Kasus pada Peserta Didik Sekolah Menengah: Strategies for Improving Literacy and Student Interest in Learning: A Case Study of Secondary School Learners - Wala, Gevan Naufal (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study examines strategies to improve literacy and interest in learning among secondary school students in Indonesia. The research used a mixed methods approach with 150 students and 25 teachers from three secondary schools in West Java as participants. Data were collected through observation, interviews, questionnaires and document analysis. The findings showed that students' initial literacy level was moderate (65.4%), with significant variations across different types of literacy. Interest in learning is mainly influenced by teaching methods (42.3%), learning environment (28.7%) and technology integration (16.5%). The research identified effective strategies at the policy, classroom and community levels, including the implementation of a daily 15-minute reading program, the integration of technology-based literacy activities and the establishment of literacy partnerships between parents and schools. These strategies showed significant improvements in students' reading habits (increased by 27.8%) and overall academic performance (increased by 18.6%). The study concludes that a comprehensive approach involving school policies, innovative teaching strategies, parental involvement and technology integration is essential for improving literacy and interest in learning among secondary school students.